Modeling and characteristics investigation of self-regulating HTS flux pump. (June 2022) - Zhai, Yao; Ma, Guangtong; Deng, Yuke; Sun, Chenzhen; Li, Yuxiao; Zhou, Pengbo
Highlights: Establish an accurate model in Matlab/Simulink to characterize the working performance of self-regulating high temperature superconducting (HTS) flux pump from a view of circuit. This model is able to reproduce the experimental results with a pretty good agreement, and can be used to investigate the impact of the corresponding geometrical and electromagnetic parameters in the system. Abstract: Self-regulating high temperature superconducting (HTS) flux pump is a promising candidate for realizing the quasi-persistent current mode operation of closed-loop HTS magnets. To characterize its performance and optimize accordingly, in this work, we have established a model in Matlab/Simulink. The effectiveness of the model has been validated based on the data obtained from the previous experimental counterpart. The calculated results show that this model is able to reproduce the experimental results with a satisfactory agreement. Based on the exploration of the model, we found that the charging performance of self-regulating HTS flux pump is mainly dependent on a range of typical design considerations, including the length of HTS bridge, the applied frequency of power source, the coupling coefficient of magnetic couplers, as well as the scale of HTS coils. Additionally, we proved that the charging speed can be accelerated and the saturated load current will correspondingly increase with the appropriate system parameters. The results obtained by this work provide some useful references for further optimization design of self-regulating HTS flux pump devices.